Comparison of clinical aspects and Mantoux test in tuberculosis versus non-tuberculosis superficial lymphadenitis - Siti Nilawardhani; Helmi Lubis; Ridwan M Daulay; Gabriel Panggabean; Siti Mirhalina Hasibuan (Indonesian Pediatric Society Publishing House, 2016)
Objective To investigate the clinical aspects and result of Man- toux test in superficial lymphadenitis caused by Mycobacterium tuberculosis (MTB) compared to that caused by non-MTB organ- isms. Methods This was a cross sectional study conducted on 86 pa- tients aged between 3 months and 14 year-old with enlargement of the superficial lymph nodes, 43 with tuberculosis superficial lym- phadenitis (TSL) and 43 with non-tuberculosis superficial lymphad- enitis (NTSL). The diagnoses of TSL and NTSL were confirmed by histopathological examination. Clinical symptoms and Mantoux test were examined in this study. Results In the TSL group, most children (70%) were in the age of >5-14 year-old, while in the NTSL, most (46%) were 1-5 years old. The most frequent chief complaint in the TSL group was fever (37%), while in the NTSL group, cough (49%) (p=0.004). Failure to thrive and loss of appetite were more frequently found in the TSL (70% and 35%) compared to the NTSL group (0 and 3%) (p=0.004). Most enlarged nodes in TSL were multiple (67%), while in NTSL, solitary (72%) (p<0.001). There were no differences in the location and distribution of enlarged nodes between the two groups. Thirty- one (72%) children in the TSL group had positive Mantoux test, while in the NTSL group were only 2(5%) (p<0.001). Conclusions Most children with TSL had fever as the chief com- plaint while those with NTSL had cough. Children with TSL had failure to thrive, loss of appetite, multiple nodes, and positive Man- toux test more frequently compared to NTSL ones